Program Student Visit dalam Pameran Plastics and Rubber Indonesia 2023 PT Pamerindo Indonesia - Syam, Hilmi Sofya Angelina; Setyawan, Heri (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
This study examines the impact of the Student Visit Program on active learning among university students attending the